To expand 74(8h+3), we use the distributive property, which states that for any three numbers a, b, and c, a(b + c) = ab + ac.
So, applying the distributive property, we have:
74(8h + 3) = 74 * 8h + 74 * 3
= 592h + 222
So, the expanded form of 74(8h+3) is 592h + 222.
Expand 74(8h+3)
3 answers
Expand 7/4(8h+3)
To expand 7/4(8h+3), we use the distributive property, which states that for any two numbers a and b and a third number c, a(b + c) = ab + ac.
So, applying the distributive property, we have:
7/4(8h + 3) = (7/4) * 8h + (7/4) * 3
To simplify further, we can multiply each term separately:
= (7/4) * (8h) + (7/4) * (3)
= (7 * 8h) / 4 + (7 * 3) / 4
= 56h / 4 + 21 / 4
Now, we can combine like terms by adding the numerators:
= (56h + 21) / 4
So, the expanded form of 7/4(8h+3) is (56h + 21) / 4.
So, applying the distributive property, we have:
7/4(8h + 3) = (7/4) * 8h + (7/4) * 3
To simplify further, we can multiply each term separately:
= (7/4) * (8h) + (7/4) * (3)
= (7 * 8h) / 4 + (7 * 3) / 4
= 56h / 4 + 21 / 4
Now, we can combine like terms by adding the numerators:
= (56h + 21) / 4
So, the expanded form of 7/4(8h+3) is (56h + 21) / 4.